ANALISIS PENGARUH EFEKTIVITAS KOMITE AUDIT, JENIS AUDITOR DAN KARAKTERISTIK PERUSAHAAN TERHADAP KETEPATAN WAKTU PELAPORAN PERUSAHAAN - Setyaningrum Setyaningrum; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2019)
This research aims to examine the influence of audit committee effectiveness and type of auditor on the timeliness of reporting in Indonesia. This reserach used financial condition, firms size and type of industry as control variable.This research uses secondary data which obtained from date of publication of the financial statement and annual reports of company listed on the Indonesia Stock Exchange in 2017 and consist of manufacture, construction, and service company. The number of research samples is 204 company samples and determined by purposive sampling method. Multiple regression analysis is used to test the hypothesis.The results of research that have been completed show that audit committee effectiveness and type of auditor have a significant negatively with financial reporting lead time.